PEMANFAATAN MICROCONTROLLER ARDUINO UNO UNTUK SISTEM MONITORING SUHU DAN KELEMBABAN KUMBUNG JAMUR TIRAM - Faizah, Arbiati; Hari Saputro, Pujo; Augusta Jannatul Firdaus, Reza (Inovate, 2019)
Mushrooms are a high source of nutrition and can be processed into various types of cuisine. Oystermushroom cultivation in low-lying areas requires controlling temperature and humidity in mushroomkumbung to get optimal growth. Currently the system of regulating the temperature and humidity ofmushroom kumbung is done manually and automatically. This study aims to design and create anautomatic temperature and humidity monitoring system for oyster mushroom kumbung by utilizing anArduino Uno microcontroller and a DHT11 temperature sensor. The system design is made throughtwo phases namely hardware design and software design. The hardware design using the Arduino Unomicrocontroller and DHT11 sensor aims to monitor the temperature and humidity of the kumbung andsend data to the server. Whereas hardware design is implemented in an android application as aninterface in receiving data from the server and delivering the results of temperature and humiditymonitoring to farmers. The system that was made has been implemented in the oyster mushroomkumbung and tested temperature and humidity successfully and can send data to the server.Keywords: Arduino Uno, Microcontroller, Sensor DHT 11, Monitoring System.